2023
DOI: 10.1111/cea.14298
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane corner: Pulmonary rehabilitation for adults with asthma

Abstract: In 2016, asthma management was estimated to cost £1.1 billion in primary care services, disability claims and hospital services in the UK. 1 The NHS long-term plan encourages referrals to Pulmonary Rehabilitation (PR) services for patients with some chronic respiratory diseases due to evidence for its cost-effectiveness in reducing symptoms and hospital admissions. 2 This review 3 explored the use of PR in asthma management with the hypothesis that its combination of educational and exercise components could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The review did not include any study where diagnostic asthma tests were used in identifying asthma outcomes. 9 Overall, the results were mixed in almost all groups but no adverse treatment effects of the interventions were reported.…”
Section: Commentarymentioning
confidence: 95%
See 1 more Smart Citation
“…The review did not include any study where diagnostic asthma tests were used in identifying asthma outcomes. 9 Overall, the results were mixed in almost all groups but no adverse treatment effects of the interventions were reported.…”
Section: Commentarymentioning
confidence: 95%
“…However, the evidence was deemed very uncertain for both due to differences in scales and unknown minimal clinically important differences (MCID). The review did not include any study where diagnostic asthma tests were used in identifying asthma outcomes 9 …”
Section: Commentarymentioning
confidence: 99%
“…This month's Cochrane Corner summarizes evidence for pulmonary rehabilitation for treating adults with asthma 8 . The authors found that this non‐drug approach to treating asthma improves quality of life and functional exercise capacity.…”
Section: Figurementioning
confidence: 99%